Differentiation Potential of Mesenchymal Stem/Stromal Cells Is Altered by Intrauterine Growth Restriction - Weatherall, Emma L.; Avilkina, Viktorija; Cortes-Araya, Yennifer; Dan-Jumbo, Susan; Stenhouse, Claire; Donadeu, Francesc X.; Esteves, Cristina L. (Frontiers in Veterinary Science, 2020)
Consistency in clinical outcomes is key to the success of therapeutic Mesenchymal Stem/Stromal cells (MSCs) in regenerative medicine. MSCs are used to treat both humans and companion animals, horses, dogs and cats. The properties of MSC preparations can vary significantly with factors including tissue of origin, donor age or health status. We studied the effects of developmental programming associated with intrauterine growth restriction (IUGR) on MSC properties, particularly related to multipotency. IUGR results from inadequate uterine capacity and placental insufficiency of multifactorial origin. Both companion animals (horses, dogs, cats) and livestock (pigs, sheep, cattle) can be affected by IUGR resulting in decreased body size and other associated changes that can include, alteration in musculoskeletal development and composition, and increased adiposity. This has consequences on health and performance in adult life and, in the case of farm animals, on meat quality. In humans, IUGR is linked to increased risk of metabolic (type 2 diabetes, cardiovascular) and other diseases later in life. Here, we studied porcine MSCs where IUGR occurs spontaneously, and shows features that recapitulate human IUGR. We compared the properties of adipose-derived MSCs from IUGR (IUGR-MSCs) and Normal (Normal-MSCs) newborn pig littermates. Both MSC types grew clonally and expressed typical MSC markers (CD105, CD90, CD44) at similar levels. Importantly, tri-lineage differentiation capacity was significantly altered by IUGR. IUGR-MSCs had higher adipogenic capacity than Normal-MSCs as evidenced by higher adipocyte content and expression of the adipogenic transcripts, PPARγ and FABP4. A similar trend was observed for fibrogenesis, where, upon differentiation, IUGR-MSCs expressed significantly higher levels of COL1A1 than Normal-MSCs. In contrast, chondrogenic and osteogenic potential were decreased in IUGR-MSCs as shown by a smaller chondrocyte pellet and osteocyte staining, and lower expression of SOX9 and RUNX2, respectively. In conclusion, the regenerative potential of MSCs appears to be determined prenatally in IUGR and this should be taken into account when selecting cell donors in regenerative therapy programmes both in humans and companion animals.